Hyers-Ulam and Hyers-Ulam-Rassias Stability of Nonlinear Volterra-Fredholm Integral Equations - Hamoud, Ahmed A.; Mohammed, Nedal M. (Discontinuity, Nonlinearity, and Complexity, 2026)
Two new stability results, Hyers-Ulam stability and Hyers-Ulam-Rassias stability, of a class Volterra-Fredholm integral equations are presented by using a fixed point theorem in a generalized complete metric space. In addition, for corresponding Volterra-Fredholm integral equations on infinite intervals the Hyers-Ulam-Rassias stability is also obtained.